Analisis Penggambaran Experiential Marketing dalam Iklan Le Minerale 2024 - Hidayatullah, Sulthon; Agustini, Vilya Dwi; Tiara, Andys (Brand Communication, 2025)
Advertising this is media product that has the aim of persuading consumers to purchase a product. Experiential marketing which consists of 5 elements is a way for a company to attract consumers, which is then done by Le Minerale as a drinking water brand in Indonesia. Qualitative Content Analysis is used to analyze how the depiction of experiential marketing messages carried out by Le Minerale. The results found that the 5 elements of Experiential marketing were maximized in Le Menineral advertisements, they used the momentum of international tournaments by featuring several national figures who took part in international events.